THE VALUE OF CITIZENSHIP IN SHAPING ISLAMIC CHARACTER IN MAN BINJAI STUDENTS - Fathir Rizky; Faris Hibatullah Siregar; Ahmad Arief; Rahmansyah Fadlul Al Karim Rambe (Pena Cendekia Insani, 2024)
To form a religious character while still holding fast to civic values, moreover we want to make students as citizens who have good morals and are responsible to their country, it is very important for us to educate students about the values contained in Pancasila. In which Pancasila itself has 5 values including the values of divinity, humanity, unity, democracy, and justice. These values certainly have one purpose and goal, namely to create students who are nationalist but still have a religious character based on the Qur'an and Sunnah, and this hope will create a prosperous society and nation